2020
DOI: 10.1016/j.isci.2020.101586
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Controlled Porous Crystalline Silicon Lithium Metal Batteries

Abstract: Summary Nanostructured porous silicon materials have recently advanced as hosts for Li-metal plating. However, limitations involve detrimental silicon self-pulverization, Li-dendrites, and the ability to achieve wafer-level integration of non-composite, pure silicon anodes. compo. Herein, full cells featuring low-resistance, wafer-scale porous crystalline silicon (PCS) anodes are embedded with a nanoporous Li-plating and diffusion-regulating surface layer upon combined wafer surface cleaning (SC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, and in contrast to solid electrolyte composed silicon electrodes, silicon wafers are stable in ambient conditions, which would avoid the need for specialized facilities to maintain dry conditions during solid state anode fabrication. Several previous studies have reported the fundamental mechanisms of electrochemical lithium insertion in silicon wafers in liquid electrolyte systems. However, in this study, we report on the outstanding performance of silicon wafer cells in solid electrolyte systems, achieving an increased cycle retention of up to 100 cycles by controlling the surface morphology. Additionally, we have successfully operated a full-cell with a Ni-rich NCM cathode.…”
mentioning
confidence: 78%
“…Furthermore, and in contrast to solid electrolyte composed silicon electrodes, silicon wafers are stable in ambient conditions, which would avoid the need for specialized facilities to maintain dry conditions during solid state anode fabrication. Several previous studies have reported the fundamental mechanisms of electrochemical lithium insertion in silicon wafers in liquid electrolyte systems. However, in this study, we report on the outstanding performance of silicon wafer cells in solid electrolyte systems, achieving an increased cycle retention of up to 100 cycles by controlling the surface morphology. Additionally, we have successfully operated a full-cell with a Ni-rich NCM cathode.…”
mentioning
confidence: 78%
“…Diffusion in crystalline materials 31 finds many applications in industrial domains such as micro-electronics, 32,33 energy, 34,35 nuclear, 36,37 and corrosion 38 for instance. For such applications, it is necessary to link the atomic scale description to the macroscopic scale features for the design and/or optimization toward the tailored final properties.…”
Section: Diffusion In Crystalline Materialsmentioning
confidence: 99%